ANALISA CAPITAL ADEQUACY RATIO (CAR), RETURN ON ASSET (ROA), NON PERFORMING FINANCING (NPF), DAN FINANCING TO DEPOSIT RATIO (FDR) BANK PANIN DUBAI SYARIAH SEBELUM DAN SESUDAH IPO PERIODE 2011-2017 - Dhevy Ulinnuha Sholichah; Dian Filianti (Universitas Airlangga, 2019)
This research analyzed the difference between sharia bank’s financial performance before and after IPO period 2011-2017. Common Sharia Bank that match the criteria is Panin Dubai Syariah Bank. Data used in this research is secondary data that collected from bank’s annual financial statements. Financial ratios used as variables in this research are Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Return On Assets (ROA), and Financing to Deposit Ratio (FDR). The results that tested using Paired T-Test and Wilcoxon Signed Rank Test shows that CAR, NPF, ROA, and FDR on Panin Dubai Syariah Bank indicate there’s significantly difference between before and after IPO. The significantly differences indicated using significance levels of 1%, 5%, and 10%.Keywords: Sharia Bank, Financial Performance, CAR, NPF, ROA, FDR, Initial Public OfferingREFERENCES Abdillah, Willy dan Jogiyanto Hartono M. 2015. Partial Least Square (PLS). Yogyakarta: Penerbit Andi.Alanazi, Ahmed S. and Benjamin Liu. 2013. IPO Financial and Operating Performance: Evidence from the Six Countries of the GCC, (Online), (https://www.researchgate.net diakses tanggal 12 Januari 2018). Ansori, Muslich dan Sri Iswati. 2009. Metodologi Penelitian Kuantitatif. Surabaya: Airlangga University Press. Az-Zuhaili, Wahbah. 2013. Tafsir Al-Munir jilid 2 (Juz 3-4). Penerjemah: Abdul Hayyie al-Kattani, dkk. Jakarta: Gema Insani.Bank Indonesia. 2013. Pedoman Akuntansi Perbankan Syariah Indonesia.Bank Panin Dubai Syariah. Laporan Keuangan Triwulan Bank Panin Dubai Syariah Bulan Maret 2011 - Desember 2017, (Online). (www.paninbanksyariah.co.id, diakses tanggal 1 Desember 2017).Danupranata, Gita. 2013. Manajemen Perbankan Syariah. Jakarta: Salemba Empat.Dendawijaya, Lukman. 2009. Manajemen Perbankan. Jakarta: Ghalia Indonesia.Departemen Agama Republik Indonesia. 2002. Al Quran dan Terjemahannya. Jakarta: Departemen Agama Republik IndonesiaFitriani, Riska Nurul dan Sasi Agustin. 2016. Analisis Kinerja Keuangan Sebelum dan Sesudah Go Public. Jurnal Ilmu dan Riset Manajemen, (Online), Vol. 5, No. 7, (https://ejournal.stiesia.ac.id/ diakses tanggal 12 Februari 2018). Ghozali, Imam. 2013. Aplikasi Analisis Multivariate Dengan Program IBM SPSS 21. Semarang: Badan Penerbit Universitas Diponegoro.Hutagalung, Esther Novelina, Djumahir, dan Kusuma Ratnawati. 2013. Analisa Rasio Keuangan terhadap Kinerja Bank Umum di Indonesia, Jurnal Aplikasi dan Manajemen, (Online), (http://jurnaljam.ub.ac.id/ diakses tanggal 1 Maret 2018).Ikatan Bankir Indonesia. 2014. Memahami Bisnis Bank Syariah. Jakarta: PT Gramedia Pustaka Utama.Kasmir. 2016. Analisis Laporan Keuangan. Jakarta: Raja Grafindo Persada.Kuncoro dan Suhardjono. 2002. Manajemen Perbankan: Teori dan Aplikasi. Yogyakarta: BPFE. Mardani. 2015. Aspek Hukum Lembaga Keuangan Syariah di Indonesia. Jakarta: Kencana Prenadamedia Group.Muhamad. 2015. Manajemen Dana Bank Syariah. Jakarta: Raja Grafindo Persada.Munisi, Gibson Hosea. 2017. Financial Performance of Initial Public Offerings: Companies Listed on Dar es Salaam Stock Exchange. Business and Economics Journal, (Online), Vol. 8, (http://astonjournals.com/ diakses tanggal 12 Januari 2018). Peraturan Bank Indonesia Nomor 15/12/PBI/2013 Tentang Kewajiban Penyediaan Modal Minimum Bank.Peraturan Bank Indonesia Nomor 3/25/PBI/2001 Tentang Penetapan Status Bank dan Penyerahan Bank Kepada Badan Penyehatan Perbankan Nasional.Quthb, Sayyid. 2001. Tafsir Fi Zhilalil Qur’an di Bawah Naungan Al-Qur’an Jilid 4. Jakarta: Gema Insani Press. Surat Edaran Bank Indonesia Nomor 13/24/DPNP Tanggal 25 Oktober 2011.Surat Edaran Bank Indonesia Nomor 3/30/DPNP Tanggal 14 Desember 2001.Sutedi, Adrian. 2011. Pasar Modal Syariah. Jakarta: Sinar Grafika.Tandelilin, Eduardus. 2010. Portofolio dan Investasi. Edisi Pertama. Yogyakarta: Kanisius.Umam, Khaerul. 2013. Manajemen Perbankan Syariah. Bandung: Pustaka Setia.Undang-undang Republik Indonesia Nomor 21. 2008. “Undang-undang Republik Indonesia Nomor 21 Tahun 2008 tentang Perbankan Syariah”Undang-undang Republik Indonesia Nomor 8. 1995. “Undang-undang Republik Indonesia Nomor 8 Tahun 1995 tentang Pasar Modal” Wetik, Wilhelm A.A. 2013. Analysis of Financial Performance Pre and Post Initial Public Offering (IPO) at Bank Central Asia Tbk. Jurnal EMBA, (Online), Vol. 1, No. 4, (http://download.portalgaruda.org/article.php?article=109064&val=1025, diakses tanggal 11 Januari 2018). Widjaja, Gunawan dan Wulandari Risnamanitis, D. 2009. Seri Pengetahuan Pasar Modal: Go Public dan Go Private di Indonesia. Jakarta: Kencana Prenada Media Group.Wirajunayasa, Putu Agus Agung dan I.G.A.M. Asri Dwija Putri. 2010. Analisis Kinerja Keuangan Perusahaan Sebelum dan Sesudah Initial Public Offering. Jurnal Akuntansi Universitas Udayana, (Online), Vol. 19, (https://ojs.unud.ac.id/index.php/Akuntansi/article/view/24408, diakses pada 28 Mei 2018).